Entre Quilombos: circuitos de Festas de Santo e a construção de alianças políticas entre as Comunidades Quilombolas de Salvaterra - Marajó - Pará - LIMA FILHO, Petrônio Medeiros (Universidade Federal do Pará, 2023)
This study is an interpretation of the associations involving holy parties and political alliances between maroon communities located in the municipality of Salvaterra - Marajó - Para, based on ethnographic research conducted in maroon community of Bacabal. These maroon communities are: Salvá, Mangueiras, Caldeirão, Bairro Alto, Pau Furado, Bacabal, Santa Luzia, Providencia, Deus Ajude, São Benedito da Ponta, Siricari, Boa Vista, Paixão, União/Campina and Rosário they have in common besides conducting and participating in some of the other parties, also the fact they are the same self-defined remaining quilombo communities and are fighting for recognition and titling of their territories. To interpret the relationships between parties and political alliances, the study takes the gift paradigm or paradigm of the alliance and the association proposed by Alain Caille (2002) as the main theoretical framework. The parties in this study are interpreted as gifts that move between communities to create stronger bonds, bonds of trust and loyalty, and political alliances between them.